A tale of two fields: Management legacy, soil health, and productivity. Issue 2 (7th September 2022) - Svedin, Jeffrey; Kitchen, Newell R.; Ransom, Curtis J.; Veum, Kristen S.; Myers, Robert L.
Abstract: Adjacent fields with contrasting histories present an opportunity to evaluate the legacy of management on soil health (SH) and grain productivity. In 2011, two fields transitioned to no‐till grain production. During the previous 25 yr, one was pasture (pasture‐to‐grain; PTG), whereas the other was annually tilled for grain cropping (long‐term grain; LTG). The study objectives were to contrast these two fields relative to SH and productivity. Yield data was collected from 2011 to 2021 and SH sampled in 2021. The PTG out‐yielded LTG each year, with an average 46% yield increase. 2021 SH metrics demonstrated similar trends, with PTG 62% higher than LTG. Contrasting across fields (2020–2021), SH metrics were related to yield ( r 2 = .46–.78), but these relationships weakened when assessed within each field. These findings affirm SH indicators are sensitive to the legacy of management and are meaningful indicators of productivity across sites but less informative for within‐field variability. Core Ideas: Historic pasture maintains greater yield and soil health (SH) after a decade of grain crop production. Ten‐year average grain yield was 46% greater for a field following pasture. Across two fields, SH metrics were significantly related to grain yield ( r 2  > .46–.78). SH is sensitive to management impacts on yield rather than inherent yield variability.